Glutathione and peroxisome redox homeostasis - Maria J. Ferreira; Tony A. Rodrigues; Ana G. Pedrosa; Ana R. Silva; Beatriz G. Vilarinho; Tânia Francisco; Jorge E. Azevedo (Redox Biology, 2023)
Despite intensive research on peroxisome biochemistry, the role of glutathione in peroxisomal redox homeostasis has remained a matter of speculation for many years, and only recently has this issue started to be experimentally addressed. Here, we summarize and compare data from several organisms on the peroxisome-glutathione topic. It is clear from this comparison that the repertoire of glutathione-utilizing enzymes in peroxisomes of different organisms varies widely. In addition, the available data suggest that the kinetic connectivity between the cytosolic and peroxisomal pools of glutathione may also be different in different organisms, with some possessing a peroxisomal membrane that is promptly permeable to glutathione whereas in others this may not be the case. However, regardless of the differences, the picture that emerges from all these data is that glutathione is a crucial component of the antioxidative system that operates inside peroxisomes in all organisms.